The Impact of Restrictive Family Presence Policies in Response to COVID-19 on Family Integrated Care in the NICU: A Qualitative Study. (April 2022) - McCulloch, Holly; Campbell-Yeo, Marsha; Richardson, Brianna; Dol, Justine; Hundert, Amos; Dorling, Jon; Whitehead, Leah; MacRae, Gail; Bishop, Tanya; Afifi, Jehier; Earle, Rebecca; Rose, Annette Elliott; et al.
Objectives: To conduct a needs assessment with families and their healthcare team to understand the impact of restrictive family presence policies in the neonatal intensive care unit (NICU) in response to COVID-19. Background: In response to the COVID-19 pandemic, significant restrictive family presence policies were instituted in most NICUs globally intended to protect infants, families, and HCPs. However, knowledge on the impact of the stress of the pandemic and policies restricting family presence in the NICU on vulnerable neonates and their families remains limited. Methods: Individuals were eligible to participate if they were a caregiver of an infant requiring NICU care or a healthcare provider (HCP) in the NICU after March 1, 2020. Semi-structured interviews were conducted using a virtual communication platform, and transcripts were analyzed using inductive thematic qualitative content analysis. Results: Twenty-three participants were interviewed (12 families and 11 HCPs). Three themes emerged: (1) successes (family-integrated care, use of technology), (2) challenges (lack of standardized messaging and family engagement, impact on parental wellbeing, institutional barriers, and virtual care), and (3) moving forward (responsive and supportive leadership). Conclusions: Our findings highlight the significant impact of family restrictions on the mental well-being of families, physical closeness with parents, and empathetic stress to HCPs. Further study of potential long-term impact is warranted.